Refugees' time investments—Differences in the time use of refugees, other immigrants, and natives in Germany - Kuhlemann, Jana (Frontiers in Human Dynamics, 2022)
Since the 2015/16 refugee influx to Germany and other European countries, these host societies have been challenged with the integration of culturally distant refugees. These recent arrivals can strategically invest their time in activities promoting their integration, thereby rendering time use as a channel of integration. Refugees are a vulnerable group that differs from other immigrants with respect to their migration motivation, experience, and conditions in the receiving countries. Accordingly, refugees might also differ from other immigrants with respect to their time use. This might play a role in explaining differences in refugees’ and other immigrants’ integration outcomes. Using a cluster analysis approach, this contribution (1) descriptively examines whether and to what extent refugees’ time use differs from that of other immigrants and the host-country population in Germany and (2) examines the role of refugees’ legal status for their time use. The study examines time allocation to different activities of refugees, other first-generation immigrants, and native Germans, using data collected from 2016 to 2019 of the German Socio-Economic Panel, including the IAB-BAMF-SOEP Survey of Refugees and the IAB-SOEP Migration Sample. Results from (1) the cluster analysis approach show different clusters of time use patterns for the three population groups of refugees, other immigrants, and natives. For native Germans and other immigrants, the dominant time use cluster is characterized by full-time investment in employment activities. For refugees, the dominant time use pattern is characterized by low overall invested hours to the measured activities (low activity cluster). In contrast to the other two groups, a cluster of refugees predominantly allocating their time to employment activities is not found. Pooled analyses (2) of the role of refugees’ legal status show some evidence that those who have a form of protection status, in comparison to those who have asylum seeker status, have a lower probability to display childcare- and household-related activities than to report low activity. However, fixed effects analyses show that refugees receiving a positive decision on their asylum application do not change with respect to their time use patterns.